2017
DOI: 10.1186/s13104-017-2805-4
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cortisol in saliva: a comparison of measurement error within and between international academic-research laboratories

Abstract: ObjectiveHundreds of scientific publications are produced annually that involve the measurement of cortisol in saliva. Intra- and inter-laboratory variation in salivary cortisol results has the potential to contribute to cross-study inconsistencies in findings, and the perception that salivary cortisol results are unreliable. This study rigorously estimates sources of measurement variability in the assay of salivary cortisol within and between established international academic-based laboratories that speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…Calvi et al. (2017) found that measurement error in saliva samples due to within and between laboratory sampling was minimal.…”
Section: Methodsmentioning
confidence: 99%
“…Calvi et al. (2017) found that measurement error in saliva samples due to within and between laboratory sampling was minimal.…”
Section: Methodsmentioning
confidence: 99%
“…Salivary cortisol levels were measured using enzyme-linked immunosorbent assay kits supplied commercially for single measurements; the supplied standards were assayed in duplicates (R&D Systems, Minneapolis, MN, USA). The intra- and inter-assay coefficients of variation for salivary cortisol were 6.9% 1.9% and 9.9% 0.8%, respectively, which are both within recommended ranges [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, good practice in reporting CVs is not always observed. Inter- and intra-assay CVs within laboratories reported by Calvi et al [126] on measurements of cortisol in saliva are reported as point estimators, and neither confidence intervals nor statistical test is provided. Reed et al [127] reported the variability of measurements (thirty-three laboratories with fifteen repeated measurements on each lab) of human serum antibodies against Bordetella pertussis antigens by ELISA method using just the CVs (no associated 95% confidence intervals) in relation with the expected fraction of pairs of those measurements that differ by at least a given factor ( k ).…”
Section: Diagnostic Tests and Statistical Methodsmentioning
confidence: 99%